Indigenous Peoples, Ethnic Identity, and Poverty in Mexico Urban Profile : An Exploratory Study - World Bank (World Bank, Washington, DC, 2021)
While information exists on the process of indigenous migration to urban centers, there is very little systematic data on the current situation of urban indigenous populations in Mexico. This study analyzes the situation of five indigenous ethnic groups in three urban centers of Mexico: (a) the Mazahuas, Otomis, and Triquis in Mexico City; (b) the Mayas in Cancun; and (c) the Zapotecos in Coatzacoalcos. The study collected qualitative and quantitative data on indigenous migrant households selected from the five ethnic groups. This study used ethnographic field work to identify the interview sample within municipalities in the three cities based on global census data for municipalities and delegations. A total sample of 869 households was selected and socio-economic information collected on 4,291 household members. Finally, focus groups (defined by gender and age) were identified and interviewed using a questionnaire designed with the assistance of neighborhood leaders. This report summarizes the initial findings from analysis of the data collected from these various research instruments.